2023
DOI: 10.1111/sltb.12999
|View full text |Cite
|
Sign up to set email alerts
|

The Suicide Dot Probe Task: Psychometric properties and validity in relation to suicide‐related outcomes

Megan L. Rogers,
Catarina L. Carosa,
Lauren A. Haliczer
et al.

Abstract: BackgroundAttentional biases to suicide‐related stimuli have been linked to suicide‐related outcomes. However, behavioral tasks that have been previously modified to capture suicide‐specific attentional biases have demonstrated inconsistent reliability and validity. Adaptation of the Dot Probe Task, a computerized assessment that has been adapted to study a wide variety of biases, may be a promising candidate for assessing suicide‐specific biases.MethodsIn 280 recently discharged inpatients (51% male; Mage = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Beyond the combination of structured and unstructured interviews with clinical questionnaires, the assessment of neuropsychological abilities, such as attention and impulsiveness by a GoNoGo task [ 193 ] or the preference for negative stimuli in a dot-probe task [ 194 ], has been recently proposed as a candidate for assessing suicide-specific biases in adults’ population. Previous studies have identified physiological markers that may help identify suicidal patients, including changes in heart rate or breathing as a response to the dysregulation of the interplay between parasympathetic and sympathetic branches of the autonomous nervous system [ 195 , 196 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the combination of structured and unstructured interviews with clinical questionnaires, the assessment of neuropsychological abilities, such as attention and impulsiveness by a GoNoGo task [ 193 ] or the preference for negative stimuli in a dot-probe task [ 194 ], has been recently proposed as a candidate for assessing suicide-specific biases in adults’ population. Previous studies have identified physiological markers that may help identify suicidal patients, including changes in heart rate or breathing as a response to the dysregulation of the interplay between parasympathetic and sympathetic branches of the autonomous nervous system [ 195 , 196 ].…”
Section: Discussionmentioning
confidence: 99%